Hearing loss in neonates and infants - Goun Choe; Su-Kyoung Park; Bong Jik Kim (The Korean Pediatric Society, 2023)
Hearing in neonates and infants is crucial for their development of language and communication skills. Unless hearing loss is appropriately managed early, it can cause a significant socioeconomic burden considering its detrimental impact on the child's development and its common nature. It is also the most common congenital sensory deficit, with an approximate incidence of 1.5 per 1,000 newborns. Its etiologies are heterogeneous: genetic causes are reportedly involved in up to 80% of cases, while congenital cytomegalovirus infection is the leading environmental factor contributing to congenital hearing loss. The introduction of newborn hearing screening using automated auditory brainstem response and/or automated otoacoustic emission in many developed countries has helped detect and manage hearing loss early. Current auditory rehabilitation options such as cochlear implantation implementing cutting-edge technologies can treat almost all degrees of hearing loss, emphasizing the importance of early hearing detection and intervention. Rapidly developing genetic diagnostic technologies and future cutting-edge treatment options, including gene therapy, will shed light on the future management of hearing loss in neonates and infants.